You can just simplify to make an equivalent equation:
(2)(3x + 8) = 5 ⇒ 6x + 16 = 5
Answer:
![\boxed{\bf~6x + 16 = 5}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cbf~6x%20%2B%2016%20%3D%205%7D)
Hope it helped,
BioTeacher101
<em>(If you have any questions feel free to ask them in the comments)</em>
Answer:
a
Step-by-step explanation:
because the rest aren't true
Answer:
5P= 2P+21+45 ( sum of two sides is is equal to
the opposite exterior angle)
5P=2P +61
5P-2P=61
3P=61
p= 61÷3
p=2.33333
Answer:
g(x) = - x² - x + 12
Step-by-step explanation:
Given
g(x) = (- x - 4)(x - 3)
Each term in the second factor is multiplied by each term in the first factor, that is
- x(x - 3) - 4(x - 3) ← distribute both parenthesis
= - x² + 3x - 4x + 12 ← collect like terms
= - x² - x + 12 ← in standard form
1. - B) <span>the diameter is 16
2. - C.) </span><span>diameter is 8
3. - D.) </span><span>a circle's circumference divided by its diameter.
4. - C.) </span><span>the radius.
5. - A.) 9.42
6. - D.) </span><span>16 inches or less.
7. - A.) </span><span>π
8. - B.) </span><span>2 (3.14) π
9. - A.) 8
10. - B.) Perimeter
Hope this helps!</span>